Competitive endogenous RNA in colorectal cancer: A systematic review - Shuwen, Han; Qing, Zhou; Yan, Zheng; Xi, Yang (Gene, 2018)
Colorectal cancer is one of the most common malignant tumours. Competitive endogenous RNA (ceRNA) networks have been hypothesized, in which various RNAs regulate each other's expression using microRNA response elements (MREs). Recent evidence has highlighted the crucial regulatory roles of ceRNA networks in colorectal cancer. In this review, we summarize the present research methods as well as the currently known ceRNA competitors and targets in colorectal cancer. In addition, we discuss the significance of ceRNA and shortcomings of current studies of colorectal cancer. •ceRNA network plays important roles in the occurrence and development of colorectal cancers.•Most studied demonstrated lncRNA and miRNA were involved into the ceRNA regulation.•We summarized the ceRNA competitors and targets as well as the research methods used in colorectal cancer studies